Marvel Comics in The Context of Literary Tourism - Darma, Diana Budi; Chakim, Nur; Nur Abida, Fithriyah Inda (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study aims at discussing Marvel comics as a part of literary tourism. Marvel comics play an important role in supporting tourism development. The worldwide popularity of Marvel comics has also increased the popularity of the places that used as the setting in the comics. This study used literature review with a qualitative descriptive approach. The data is identified, classified and then interpreted based on a literary tourism and literary events. The results of the study shows that the representation of places in comic books can pique readers' interest in visiting those places. This popularity has an effect on rising tourism-related factors, monetary gains, state income, and the promotion of regional culture.